FETAL –DERIVED MACROPHAGES PERSIST AND SEQUENTIALLY MATURATE IN OVARIES AFTER BIRTH IN MICE - Kiviranta, Miikka (My University, 2020)
Macrophages and monocytes are a diverse group of white blood cells, which hold a critical role in the immune system but also carry out important functions in tissue development, homeostasis and inflammation. Thus far the developmental origin of macrophages has been widely studied in many tissues but not in ovaries. The purpose of this study was to investigate the developmental origin and functions of macrophages in ovaries in mice. We identified macrophage populations based on protein surface markers using single-cell mass cytometry. We performed ontogenic analysis with cell fate mapping models and cell depletion experiments. In addition, we studied the scavenging functions and localisation of macrophages in the ovarian tissue using antibody uptake assays and immunofluorescence staining. We identified three tissue monocyte populations and five macrophage populations in the ovaries of adult mice. Our fate mapping models revealed that macrophages from both the embryonic yolk sac and fetal liver contribute to the fetal ovarian macrophage pool. Furthermore, we found that both embryonic and adult bone marrow-derived macrophages contribute to the ovarian macrophage pool in adulthood. Moreover, our study shows how fetal MHC II-negative macrophages differentiate postnatally into MHC II-positive macrophages in maturing ovaries. Finally, we uncovered that developmentally distinct macrophages share a similar subtissular distribution and scavenging functions. In this study, we present the composition of the ovarian macrophage pool in consecutive developmental stages. In particular, we describe how monocyte immigration mechanisms, macrophage pool phenotypes and the interconversional capacity of fetalderived macrophages are unlike those seen in other tissues.
Keywords: Macrophages, monocytes, ovaries, developmental origin